Of NLP in business processes - Бойченко, М. Ю. (ХНУРЕ, 2023)
The given work is devoted to NLP the, that stands for Natural Language Processing, it is proposed to consider the development and implementation of these activities on the trust in this strategy, which involves flexible and costeffective project management based on the emotional intelligence of top managers and should correspond to value-based project approach. It was given several ways that using NLP can improve business processes.